Intraoperative Electrocochleography Correlates to Outcomes in Transmastoid and Middle Cranial Fossa Superior Semicircular Canal Dehiscence Repair. Issue 1 (January 2022) - Ellsperman, Susan E.; Telian, Steven A.; Kileny, Paul R.; Welch, Christopher M.
Abstract : Objective: To determine the degree to which electrocochleography (ECoG) correlates with auditory and vestibular outcomes after repair of superior semicircular canal dehiscence (SSCD) via transmastoid (TM) and middle cranial fossa (MCF) approaches. Study Design: Retrospective review. Setting: Academic tertiary referral center. Patients: Adults with SSCD who underwent repair between 2005 and 2019. Intervention: Pre-, intra-, and postoperative ECoG. Main Outcome Measures: Patient-reported vestibular and auditory symptoms; pre-, intra-, and postoperative ECoG measures, dizziness handicap inventory (DHI) scores. Results: Forty-six patients underwent SSCD repair (40 unilateral, six bilateral) between 2005 and 2019, including 24 MCF and 28 TM approaches. There were no differences in preoperative, intraoperative, or postrepair ECoG SP/AP values between the MCF and TM groups ( p 0.12, 0.77, 0.58). Patients had subjective improvement in vestibular symptoms (or stable vestibular function in patients operated for predominantly auditory manifestations) with both approaches (MCF: 87.5%; TM: 92.3%; p 0.64). A successful outcome correlated with intraoperative SP/AP ratio normalization ( p 0.0005). Similarly, DHI scores were similar in both groups preoperatively ( p 0.66) and returned to their preoperative baseline postoperatively with both ( p 0.52). Reported vestibular symptoms persisted or worsened more often in patients with migraine (66.6% vs. 28.9%, p 0.03), and with persistently abnormal ECoG measures, though the latter was not statistically significant in this population (38% vs. 15%, p 0.10). Patients had subjective improvement or stability in auditory symptoms using either approach (MCF: 96%; TM: 100%; p 0.62), also correlating with SP/AP ratio normalization ( p 0.008). Conclusions: Correction of abnormal preoperative ECoG reliably correlates to patient symptom improvement after SSCD repair. No significant differences in postoperative outcomes were noted between patients undergoing TM versus MCF repair. Circumspection regarding the likelihood of an ideal outcome after SSCD repair should be exercised when counseling patients with concomitant migraine. Define Professional Practice Gap and Educational Need: It is not certain whether outcomes differ between the two dominant approaches for SSCD repair. Surgeons and patients would benefit from an intraoperative metric that reflects satisfactory plugging of SSCD. Learning Objective: To highlight the reliability and unique utility of intraoperative ECoG and demonstrate the correlation between ECoG correction and symptom improvement for SSCD repair. Desired Result: To report subjective and objective outcomes following SSCD repair and encourage adoption of intraoperative ECoG monitoring. Level of Evidence: Level V. Indicate IRB or IACUC: IRB review considers this study exempt (HUM00169949).